STUDI KEPUSTAKAAN MENGENAI PENERAPAN KONSELING KELOMPOK UNTUK MENINGKATKAN KEBAHAGIAAN REMAJA YANG TINGGAL DI PANTI ASUHAN - Reri Syafitri; S Silvianetri (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2022)
This study aims to determine the increase in the happiness of adolescents living in orphanages through group counseling. The author uses the library research method that explores articles or other research that discusses what the author is researching. The results of the research that the authors get are that group counseling is effective for increasing the happiness of teenagers who live in orphanages because with group counseling they are open to each other and share with each other looking for solutions to solve the problems they feel